2022
DOI: 10.1093/nar/gkac223
|View full text |Cite
|
Sign up to set email alerts
|

Functional specialization of monocot DCL3 and DCL5 proteins through the evolution of the PAZ domain

Abstract: Monocot DICER-LIKE3 (DCL3) and DCL5 produce distinct 24-nt small interfering RNAs (siRNAs), heterochromatic siRNAs (hc-siRNAs) and phased secondary siRNAs (phasiRNAs), respectively. The former small RNAs are linked to silencing of transposable elements and heterochromatic repeats, and the latter to reproductive processes. It is assumed that these DCLs evolved from an ancient ‘eudicot-type’ DCL3 ancestor, which may have produced both types of siRNAs. However, how functional differentiation was achieved after ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The pre-miRNA 5′ phosphate is held in a pocket formed by the side chains of Arg1200 and Arg1207 and by the backbone amide groups of Ala1199 and Arg1200. This recognition mechanism contrasts that of plant DCL3, in which the phosphate binds a wider pocket formed by lysine side chains (Figure S5B and S5C) (Wang et al, 2021;Chen et al, 2022).…”
Section: Featuresmentioning
confidence: 74%
“…The pre-miRNA 5′ phosphate is held in a pocket formed by the side chains of Arg1200 and Arg1207 and by the backbone amide groups of Ala1199 and Arg1200. This recognition mechanism contrasts that of plant DCL3, in which the phosphate binds a wider pocket formed by lysine side chains (Figure S5B and S5C) (Wang et al, 2021;Chen et al, 2022).…”
Section: Featuresmentioning
confidence: 74%
“…Previous reports showed that DCL3 prefers to cleave dsRNA precursors from the end with 5′ A and/or unstable sequence ( 23–25 ). Thus, we cannot exclude the possibility that the siRNAs with the 5′ A and the thermodynamically unstable ends are enriched at the DCL3-mediated cleavage steps but not at the loading step.…”
Section: Resultsmentioning
confidence: 99%
“…In rice, OsDCL3 and OsDCL5 have completely different substrate specificities, while the eudicot AtDCL3 has an intermediate preference for dsRNAs with an overhanging 5 0 triphosphate and 3 0 structure (Chen et al, 2022). This suggests that monocot DCL5 and DCL3 proteins were optimized for cognate substrates after duplication of the progenitor "eudicot-like" DCL3 protein, and this functional specialization appears to have been achieved through the accumulation of mutations in the PAZ domain (Chen et al, 2022). Therefore, it is hypothesized that DCL3 has dual functions in some eudicots, processing distinct substrates (Pol II vs Pol IV RNA) for the biogenesis of 24-nt phasiRNAs or 24-nt hc-siRNAs (Xia et al, 2019), however, future work testing protein activity should explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The DCL5 subfamily seems to have evolved from an ancient 'eudicot-type' DCL3 ancestor, able to produce 24-nt phasiRNAs, and DCL5 accumulated mutations specifying it for distinct substrates and ensuring the production of functional siRNAs (Chen et al, 2022). Thus, plants have diversified and optimized RNA silencing mechanisms to coordinate reproductive development during evolution (Chen et al, 2022). How functional differentiation of miRNA/DCL triggers and reproductive phasiRNAs was achieved, and their biological relevance, remains elusive, especially during the microsporogenesis of eudicot plants.…”
Section: Introductionmentioning
confidence: 99%